What is the impact of credit risk on financial institutions? How credit derivatives help in mitigating such risk and how they are valued? - Mantri, Pratik (2014)
The aim of this study is to illustrate in detail the Hull and White reduced form model for pricing CDS spreads and apply the model to real world bond data. Using the assumptions laid down by the model, that the interest rates are deterministic and claim and recovery rates are known, we aim to calculate CDS spreads for a number of bonds. To obtain the CDS spreads for both the reference entity in our sample, with time to maturity 1 to 8 years on 28 August 2014; bonds prices are gathered with special consideration of time to maturity and ratings held by the bond. Post this, default probabilities are calculated using the cumulative default rates obtained from S&P (Table 4, Appendix) and applied to bonds in accordance to their time to maturity. Finally, CDS spreads are calculated with recovery rates exogenously given as constant. Our results show that due to the theoretical framework of the model and its strict assumptions, it may not give accurate results when conditions are changed. Therefore, it cannot to applied in the practical life. However, the model is successful in portraying to the readers, how CDS spreads are estimated and give them a basic understanding about the same.